Concerns for halalness of halal-labelled food products among Muslim consumers in Malaysia : evaluation of selected demographic factors. - Golnaz, Rezai; Mohamed, Zainal Abidin; Shamsudin, Mad Nasir; Chong, Eddie Chew Fook (Malaysian Agricultural Research and Development Institute (MARDI), 2009)
To Muslims, food must not only be of good quality, but must be halal. This has raised concerns among Muslim consumers regarding the halalness of manufactured halal-labelled food products. This paper focuses on the concerns of Muslim consumers in Malaysia about the halalness of manufactured foods which carry the halal logo. Cross-sectional consumer data were collected in a survey of 1,560 Muslim respondents in 2008. Descriptive and Chi-square analyses were used to analyse the data collected. Consumers with higher levels of religiosity and education are more likely to be concerned about the halal status of halal-labelled food products. There were significant difference among consumers with high level of religiosity and those attending religious school. Similarly, older generation, more educated and those that come from east coast of Malaysia are also more concern. Thus, an understanding of the extent of consumers’ concerns towards the halalness of halal-labelled food products from the religious viewpoint and relevant policy formulation in ensuring halalness of food product are vital in order to make Malaysia a successful World Halal Food Hub by 2020.